The Causes of oestrus occurance during pregnancy in cows - Jawad Khadim, Jawad (University of Thi-Qar Journal of agricultural research, 2025)
Oestrus is that restricted period of sexual receptivity, characterized by intense sexual desire, when the female will seek the male and even have periods of homosexual activity in which a cow mimics a bull. True oestrus begins when the female assumes the mating stance so that the male may mount and copulate. It does not normally occur during pregnancy in farm animals, although it is known tooccur sporadically in cattle. Occurrence of heat during pregnancy has been recognized in several species including the cow (Branton, 1949) and sheep (Williams. 1946).       The incidence of oestrus during pregnancy has been    reported to lie between(1 % and 10 % ) (Donald, H.P. 1943; Donoho and Richard 1955; Erb and Morrison 1958) .    According to previous studies, 1 - 22% of pregnant cows show estrus during gestation (Thomas and Dobson 1989). Williamson et al. (1972) reported that 7.3% of cows show standing heat within 21 days of conception. Farmers may not recognize this behaviour as estrus during pregnancy and have the cow reinseminated. If this is done deep intra cervically or intrauterine, it might cause loss of the embryo and a prolonged calving interval